Post-traumatic management of condylar fracture complications - Andrew J. Sidebottom (Journal of Oral Biology and Craniofacial Research, 2022)
Management of issues following condylar fracture is dependent on the effect on joint function and pain and an assessment of the degree of deformity. The following article aims to guide the reader in the assessment of these issues and the preservation of as much as is normal as possible. “First do no harm” is a phrase coined from the writings of Hippocrates, the Greek philosopher and physician. The cases described illustrate examples of where other clinicians have advised joint replacement, but where the author has used orthognathic or less invasive techniques to preserve existing tissues and joint function and to restore facial balance. They serve as a reminder that the complete TMJ surgeon needs a good orthognathic knowledge and expertise.